Recent trends on wound management: New therapeutic choices based on polymeric carriers - Mehmet Evren Okur; Ioannis D. Karantas; Zeynep Şenyiğit; Neslihan Üstündağ Okur; Panoraia I. Siafaka (Elsevier, 2020)
Wound healing is an unmet therapeutic challenge among medical society since wound assessment and management is a complex procedure including several factors playing major role in healing process. Wounds can mainly be categorized as acute or chronic. It is well referred that the acute wound displays normal wound physiology while healing, in most cases, is seemed to progress through the normal phases of wound healing. On the other hand, a chronic wound is physiologically impaired. The main problem in wound management is that the majority of wounds are colonized with microbes, whereas this does not mean that all wounds will be infected. In this review, we address the problems that clinicians face to manage while treat acute and chronic wounds. Moreover, we demonstrate the pathophysiology, etiology, prognosis and microbiology of wounds. We further introduce the state of art in pharmaceutical technology field as part of wound management aiming to assist health professionals to overcome the current implications on wound assessment. In addition, authors review researches which included the use of gels and dermal films as wound healing agents. It can be said that natural and synthetic drugs or carriers provide promising solutions in order to meet the wound management standards. However, are the current strategies as desirable as medical society wish?